Effect of Project Based Learning and Cooperative Type Group Investigation (GI) Learning Strategies on Higher Order Thinking Ability in Biology Course - Purba, Siska Oberlina; Manurung, Binari; Mulyana, Rachmat (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research is aimed to study the effect of project based , cooperative type GI and conventional learning strategies on higher order thinking ability of graders XI SMAN 2 Pematangsiantar. This quasi experiment was implemented as pre test and post test control group design. The population was all grades XI MIA SMAN 2 Pematangsiantar in Academic Year 2014/2015, consisted of seven classes. As many as three clasess XI4 (PjBL), XI5 (GI) dan XI7 (conventional) were chosen as samples by cluster random sampling technique. Research instruments was  higher order thinking ability (Cognitive test C4-C6). The parametric assumptions showed that the data were normally distributed and homogenous. The Anacova and Tukey’s test, were used for hypothesis testing by using SPSS v.19 statistical software. The result showed that project based learning, cooperative type GI and convensional learning strategies significantly affect student higher order thinking ability (F=14.24;P=0.000). Students who were taught by project based learning strategies (77,88 ± 7,35) had significantly different higher order thinking ability compared with those who were taught with cooperative type GI (71,10 ± 6,95) (P=0.001) and conventional learning strategies (68,05 ± 10,38) (P=0.000) even thought cooperative type GI learning strategies wasn’t significantly different compared with conventional learning strategies (P=0.237). Based on the result of research can be concluded that students higher order thinking ability on project based learning had higher than cooperative type GI and conventional learning strategies.Keywords: PjBL (Project Based Learning), Cooperative GI (Group Investigation), Biology Higher Order Thinking Ability.